Social media in learning on nature: case Finnish amateur mycologists - Santaoja Minna (Emerald, 2022)
Purpose
Eco-social crises such as the loss of biodiversity call for transformative learning. This study analyzes the prospects of social media in learning about nature.
Design/methodology/approach
The study is placed in the intersection of science and technology studies, futures studies, environmental social sciences, and environmental humanities. The study draws on a qualitative case study of a mycologists' Facebook group. The empirical material was collected through digital ethnography.
Findings
Social media provides opportunities for learning about nature for many people. However, specialized naturalist social media groups are increasingly geared towards citizen science. The development may fragment the online naturalist cultures and narrow the scope for learning.
Research limitations/implications
Insights from a single case study cannot be broadly generalized. However, the case highlights significant features to consider in promoting collective learning in social media in the future.